2017
DOI: 10.1590/s1806-92902017000900003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed inoculation with Azospirillum brasilense and nitrogen fertilization rates on maize plant yield and silage quality

Abstract: -The objective of this study was to determine the effect of Azospirillum brasilense inoculation and different nitrogen (N) rates applied as topdressing on the productivity of a maize crop and the nutritional value of maize silage. Two experiments were conducted in the 2012/2013 and 2013/2014 harvests. Treatments were distributed in a randomized block design in a factorial arrangement, which consisted of two maize hybrids (AS 1572 and Defender) coupled with nitrogen rates (0, 60, 120, 240, and 480 kg ha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
0
19
0
6
Order By: Relevance
“…However, inoculation benefits were obtained only for the AS 1572 hybrid. In experiments carried out in two harvests in the municipality of Erechim, RS, Brazil, [29] had already recorded the association of A. brasilense strains Ab-V5 and Ab-V6 with the Defender hybrid for silage. The authors also reported there were differences between the studied harvests and that, in the 2012/2013 harvest, positive effects were also obtained for the AS 1572 hybrid, as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, inoculation benefits were obtained only for the AS 1572 hybrid. In experiments carried out in two harvests in the municipality of Erechim, RS, Brazil, [29] had already recorded the association of A. brasilense strains Ab-V5 and Ab-V6 with the Defender hybrid for silage. The authors also reported there were differences between the studied harvests and that, in the 2012/2013 harvest, positive effects were also obtained for the AS 1572 hybrid, as used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies determined there was an interaction between N dose and inoculation with Azospirillum spp. [16,17,27,29]. These authors determined that positive responses to inoculation depend on the use of low or average doses of N in cover, increasing the efficiency of nitrogen fertilization in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some results found in the literature highlight that, to obtain positive results, it is necessary to associate Azospirillum with nitrogen fertilization, because only the bacterium will not respond in a positive way (Hungria 2011, Skonieski et al 2017, Souza et al 2019. In addition to the biological fixation of nitrogen, A. brasilense produces some phytohormones that contribute to the growth of plants; however, maybe only phytohormones are not enough for a positive response to occur in the inoculated plant.…”
Section: Resultsmentioning
confidence: 99%
“…It mostly forms a symbiotic association with plants. Several studies have shown the potential of Azospirillum for crop improvement [46][47][48][49]. Azospirillum-inoculated wheat seedlings developed good water status; fresh weight was higher from inoculated seeds than from non-inoculated seeds.…”
Section: Azospirillummentioning
confidence: 99%